Representasi Kekerasan Dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer - Nora Afiza; Bustanuddin Lubis; Fina Hiasa (UNIB Press, 2026)
This research aims to describe the representation of violence in the novel Bumi Manusia by Pramoedya Ananta Toer using a literary sociology approach. The method used is descriptive qualitative. The data in this study are in the form of quotes of events that reflect acts of violence in the novel Bumi Manusia. Data collection techniques are reading and writing techniques. Data analysis techniques, namely, reading the novel Bumi Manusia, marking and recording, identifying, classifying, analyzing, and making conclusions. The results of this study show that: there are 4 forms of violence in the novel Bumi Manusia, namely: 1. Physical violence in the form of persecution and murder; 2. Verbal violence through mocking and demeaning words; 3. Sexual violence, in the form of rape and sexual exploitation; 4. Bureaucratic violence in the form of unfair court legal decisions, restrictions on access to education for indigenous people, and the prohibition of using Dutch in the high court for indigenous people. Violence in the novel Bumi Manusia is a representation of the oppression, injustice and inequality experienced by indigenous people in the 20th century in the Dutch East Indies.